Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4269/ajtmh.20-0631
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Determinants Associated with Blastocystis Infection in Arequipa, Peru

Abstract: Blastocystis is one of the most common protozoa in the human gut and a zoonotic organism related to unsanitary living conditions. This protozoon shows a broad distribution, unclear symptomatology, and undefined pathogenicity. In Peru, studies report the presence of Blastocystis in many regions, but the highest prevalence levels are reported in Arequipa. The aim of this study was to link Blastocystis infection with social determinants of health. We recruited and surveyed 232 infected and uninfected participants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(53 reference statements)
2
1
0
1
Order By: Relevance
“…in human fecal samples, in agreement with the results of previous studies [ 17 , 28 – 30 ]. Similarly, a detection rate of in vitro culture of 53%, 53.6%, and 51.3% were reported in previous studies [ 28 , 31 , 32 ]. On the other hand, other studies reported that PCR assay had the highest percentage of Blastocystis sp.…”
Section: Discussionsupporting
confidence: 82%
“…in human fecal samples, in agreement with the results of previous studies [ 17 , 28 – 30 ]. Similarly, a detection rate of in vitro culture of 53%, 53.6%, and 51.3% were reported in previous studies [ 28 , 31 , 32 ]. On the other hand, other studies reported that PCR assay had the highest percentage of Blastocystis sp.…”
Section: Discussionsupporting
confidence: 82%
“…These observations support the historical findings on abundance of Blastocystis in developing countries owing to poor personal hygiene, unsanitary living conditions, consumption of contaminated food and water, and exposure to animals [9,27,28]. Moreover, the prevalence of Blastocystis reported in this study is consistent with previous studies done in developing world [4,29,30]. Blastocystis is transmitted through fecal-oral route.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that occupation may be a factor favouring the frequent infection of men. Additionally, other risk factors for blastocystosis was not considered in the present study, such as living with domestic animals or water being treated before consumption [36].…”
Section: Discussionmentioning
confidence: 99%